2022
DOI: 10.1002/chem.202201899
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Structural Variation and Sodium Storage Behavior of Polyoxometalates Encapsulated within Single‐Walled Carbon Nanotubes

Abstract: The host–guest interaction can remarkably alter the physiochemical properties of composite materials. It is crucial to clarify the mechanism by revealing the influence of the host on the electronic structure of the guest molecules. Herein, we study the structural variation of polyoxometalates (POMs) after being confined in single‐walled carbon nanotubes (SWNT). What we found is that in addition to the reported charge transfer from SWNT to POM, an intramolecular electron transfer within a single POM cluster can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In addition to the electron transfer between the host and guest, Song's group clarified the influence of the confinement effect on the electronic structure of POM. [ 118 ] They found that after confining in SWCNTs, electron transfer also occurred within a single POM molecule, and more electrons accumulated on the bridged oxygen of POMs. When applied as an anode material for sodium‐ion battery (SIB), the reversible capacity of PMo 12 @SWCNTs electrode was maintained at 210 mA h g −1 after 100 cycles at a current density of 750 mA g −1 .…”
Section: Application Of Confined Pomsmentioning
confidence: 99%
“…In addition to the electron transfer between the host and guest, Song's group clarified the influence of the confinement effect on the electronic structure of POM. [ 118 ] They found that after confining in SWCNTs, electron transfer also occurred within a single POM molecule, and more electrons accumulated on the bridged oxygen of POMs. When applied as an anode material for sodium‐ion battery (SIB), the reversible capacity of PMo 12 @SWCNTs electrode was maintained at 210 mA h g −1 after 100 cycles at a current density of 750 mA g −1 .…”
Section: Application Of Confined Pomsmentioning
confidence: 99%
“…SWCNTs that encapsulate the POMs clusters strictly limit the molecular motion in two dimensions but enable the intermolecular reactions between pairs of neighboring POM clusters in the third dimension. The encapsulated POM/SWCNT system [105][106][107][108][109] enables the direct observation of cluster rotation [110] and condensation reaction [111] in a fixed dimension.…”
Section: Dynamics Of Metal Nanoclusters In Confined Spacementioning
confidence: 99%
“…13 In general, for saturated POMs, the bridge oxygen atoms act as the active sites during a redox reaction, but unfortunately, they can hardly be activated, which severely limits their photocatalytic performance. 14 To solve the problem, by removing one or more MO 6 metal octahedra from the saturated structure, the negative charge of the terminal oxygen at the deletion site remains a fixed-domain state, thus increasing the density of the electron cloud inside the vacant POMs, and finally improving the nucleophilic and catalytic reactivity. Coincidentally, for bismuth POMs, the heteroatom Bi 3+ in its structure forms a triangular cone structure with its three neighbouring oxygen atoms, and because of the presence of a lone pair of electrons at the top of this triangular cone structure, together with the repulsion of identical charges, the resulting stereochemical effect leads to the vacancy of bismuth POMs during the formation process, so that the bismuth POMs are mostly deficient in the structure, 15 which is suitable for use in the construction of photocatalytic composite materials.…”
Section: Introductionmentioning
confidence: 99%